Study guides

☆☆

Q: What is cot theta divided by tan theta plus one equal?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Until an "equals" sign shows up somewhere in the expression, there's nothing to prove.

For a start, try converting everything to sines and cosines.

are you in Kindergarten of course one plus one will equal 2

Below link may help.You need to memorize the basic formulas and it will be easy.pythagorean theoremc² = a² + b²Sine Theta (sin θ) = opposite/hypotenuse = a/cCosine Theta (cos θ) = adjacent/hypotenuse = b/cTangent Theta (tan θ) = opposite/adjacent = a/bCotangent Theta (cot θ) = adjacent/opposite = b/aSecant Theta (sec θ) = hypotenuse/adjacent = c/bCosecant Theta (csc θ) = hypotenuse/opposite = c/a

You can transform this in different ways (I suggest writing cot x as "cos x / sin x", for easier manipulation), but I doubt you can make it any simpler.

Related questions

It depends if 1 plus tan theta is divided or multiplied by 1 minus tan theta.

Yes, it is.

Since sin(theta) = 1/cosec(theta) the first two terms simply camcel out and you are left with 1 divided by tan(theta), which is cot(theta).

tan2(theta) + 5*tan(theta) = 0 => tan(theta)*[tan(theta) + 5] = 0=> tan(theta) = 0 or tan(theta) = -5If tan(theta) = 0 then tan(theta) + cot(theta) is not defined.If tan(theta) = -5 then tan(theta) + cot(theta) = -5 - 1/5 = -5.2

It is -sqrt(1 + cot^2 theta)

Cotan(theta) is the reciprocal of the tan(theta). So, cot(theta) = 1/2.

Until an "equals" sign shows up somewhere in the expression, there's nothing to prove.

-2(cot2theta)

cosec(q)*cot(q)*cos(q) = 1/sin(q)*cot(q)*cos(q) = cot2(q)

Since CotΘ = 1 / tanΘ, then tanΘ / cotΘ = tanΘ / (1/tanΘ) = tanΘ x tanΘ = tan²Θ

For a start, try converting everything to sines and cosines.

cot theta=tan(90-tetha)

People also asked